A comparative study of Tetum prepositions and Makasae postpositions - Soares, Antonio Constantino (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2025)
This study examines the syntactic roles of prepositions in Tetum and postpositions in Makasae, with a focus on their functions in conveying spatial and relational concepts. Tetum, an Austronesian language spoken in East Timor, and Makasae, a Trans-New Guinea language spoken in Timor-Leste's eastern districts, employ different syntactic structures for conveying relationships between noun phrases and other sentence elements. While Tetum uses prepositions such as "iha" (at) that precede the noun phrase, Makasae uses postpositions such as "isi e'e," "isi we'e," and "isi wo'i," which follow the noun phrase to express similar spatial relations. The research employs a qualitative methodology, using elicitation and interviews with native speakers of both languages. Native speakers of Makasae were asked to produce sentences using "isi e'e," "isi we'e," and "isi wo'i" in various syntactic contexts, while interviews provided insights into the intuitive use of these postpositions across different speech settings. The collected data was analyzed thematically to identify patterns in the syntactic behavior of these postpositions and to compare them with the prepositional system of Tetum. Findings reveal that "isi e'e," "isi we'e," and "isi wo'i" function similarly to prepositions in English, such as "in" or "at," but differ in their syntactic placement, as they follow the noun phrase in Makasae. This contrasts with the prepositional structure of Tetum, where prepositions like "iha" precede the noun phrase. Despite these syntactic differences, both languages convey spatial and relational meaning effectively, highlighting the typological diversity within the Austronesian and Papuan language families.